Investigate on dynamic mechanical and mesoscopic damage characteristics of high-temperature treated granite based on SPH-FEM coupling algorithm - Liu Zilu; Yu Weijian; Wu Genshui; Zhang Zizheng; Wang Ping (Journal of Materials Research and Technology, 2025)
High-temperature make rock engineering vulnerable to instability and failure under dynamic disturbance, investigating dynamic mechanical behavior of rocks under high-temperature conditions holds significant engineering importance. In this study, the mineral composition and mesoscopic crack characteristics of granite within the temperature range of 25–600 °C were observed using X-ray diffraction (XRD) and polarized microscopy (PM), the dynamic impact characteristics of granite at different temperatures and impact velocities were tested by separated SHPB system, a SPH-FEM coupling model in LS-DYNA software was established to investigate the dynamic fracture characteristics of granite after heat treatment. The results indicate that: as temperature increasing, the mass loss rate of the granite samples continuously increases, the volumetric expansion rate and density reduction rate first increase and then decrease, the wave velocity decreases linearly. Within the temperature range of 25∼600 °C, the quartz content remains relatively stable, while the proportion of sodium feldspar increases with temperature, and the proportion of potassium feldspar continuously decreases. The loss of various types of moisture within the rock intensifies the damage to its crystalline structure, elevated temperatures can lead to the metamorphism of the mineral components in granite, resulting in alterations to its macro-mechanical properties. The peak strength of granite samples rises with the increase in strain rate, especially at 25 °C and 150 °C. Nevertheless, for the same strain rate, the peak strength of granite decreases as the temperature increases. At same temperature, the fragmentation of granite samples increases with the strain rate, as the temperature rises, the extent of fragmentation after failure also increases for similar strain rates. The LS-DYNA model calculation results closely matched the result of experiment, at temperatures ≤300 °C, the slices showed progressive splitting failure from periphery to interior, while at temperatures ≥450 °C, the slices passing through the center exhibited a 'inverted V′ shaped failure. This study will offer both data support and theoretical insights for the stability control and safety evaluation of rock engineering under dynamic loading in high-temperature conditions.